State repression and poverty control in contemporany Brazil - Fernandes Correia, Nathália de Lourdes; Marinho de Souza, Reivan (Argumentum, 2020)
Abstract: This article proposes to unveil the economic and social determinations that have led to the deepening of the State’s repression towards poverty in Brazil. The State maintains an inseparable relationship with the economy and to fulfill its social function historically it can intervene in a repressive or coercive way. Currently, with the structural crisis, as validated by the empirical data, the increase in the State’s repressive action in Brazil reveals a massive incarceration in the country, the emergence of new repressive measures and the increase in deaths due to police intervention, as consequence of societal changes, chronic unemployment and poverty. Keywords: State Repression. Capitalism. Poverty. Structural crisis.